Redesigning Gambar Lucu Mika Book to Enhance Digital Literacy Competencies - Azzahra, Fatimah; Sunendar, Dadang; Fairus, Ferah (JURNAL PENDIDIKAN USIA DINI, 2025)
The increasing exposure of children to digital environments necessitates integrating digital literacy into educational materials. However, the Gambar Lucu Mika book, designed for early literacy development, lacks essential elements of digital safety, prompting the need for content redesign. This study aimed to enhance the book by incorporating digital safety concepts aligned with the pillars of digital literacy: Digital Skill, Digital Ethics, Digital Culture, and Digital Safety. A research and development approach were employed, involving an initial content analysis, expert validation, and iterative revisions. Data were collected through document review and expert evaluation, analyzed descriptively and qualitatively.The redesigned textbook introduces interactive scenarios, guided activities, and quizzes to teach these concepts effectively. Expert validation confirmed that the new design is relevant, practical, and feasible for elementary school use. The study concludes that integrating Digital Safety into educational materials is essential for equipping young learners with critical online security skills. This research contributes to the development of more comprehensive learning resources and offers a replicable framework for integrating digital literacy into primary educationrds.